Sonographic Evaluation of Fetal Adrenal Gland in Gestational Diabetes: Relation to Fetal Growth and Maternal Biochemical Markers. (2nd February 2017) - Garcia‐Flores, Jose; Cruceyra, Mireia; Cañamares, Marina; Garicano, Ainhoa; Espada, Mercedes; Nieto, Olga; Tamarit, Ines; Sainz de la Cuesta, Ricardo
Abstract : Objectives: To relate measurements and volume of the fetal adrenal gland in third trimester ultrasound in diabetic pregnancies (1) to birth weight; (2) to other sonographic markers of diabetic fetopathy (expected fetal weight, sectional area, and fractional volume in fetal limbs); and (3) to maternal biochemical markers of diabetes (HbA1c, leptin). Methods: Fetal adrenal gland measurements were obtained between 32 and 34 weeks. The gland length, width, depth, and volume (by Virtual Organ Computer‐Aided Analysis [VOCAL]) were measured for total gland and fetal zone. Fetal total and fat sectional area and fractional volume were obtained in arm and thigh. A maternal blood sample was obtained. Univariate and multivariate models were used to assess the associations. Results: Thirty‐nine diabetic pregnancies were included. Birth weight related significantly to total and fetal zone adrenal depth, and total adrenal volume in third trimester. Total adrenal length and corrected adrenal gland volume also showed a significant correlation to birth weight percentile in univariate and multivariate models. Total adrenal volume associated significantly to total and fat areas and volumes in fetal limbs. Both maternal leptin and HbA1c levels found a significant positive relation to fetal total adrenal volume and corrected adrenal gland volume. Total adrenal gland volume showed a significant association to maternal HbA1c level in multivariate model. Conclusions: An enlargement of the fetal adrenal gland may be observed in gestational diabetes, not only related to birth weight, but also to distinctive features of diabetic pregnancies, such as fat tissue fetal deposits or maternal biochemical markers.